Preliminary investigation on the economic cost of mitochondrial disease in Chinese children - Chaolong Xu; Dan Zhao; Xin Duan; Zhimei Liu; Tongyue Li; Yunxi Zhang; Zixuan Zhang; Tianyu Song; Ying Zou; Huafang Jiang; Fang Fang (Orphanet Journal of Rare Diseases)
Abstract Background The prevalence of mitochondrial diseases is increasing, leading to a significant economic burden on families and society. However, nationwide cost data on their effects on China’s economy remain limited. This study aimed to investigate the economic cost of mitochondrial diseases in Chinese children, analyse the relevant influencing factors, and provide a foundation for strategies to reduce the healthcare burden. Methods In this single-centre, cross-sectional study, an online questionnaire was randomly administered to paediatric patients diagnosed with mitochondrial diseases between January 2012 and January 2022. The questionnaire included questions regarding demographic data, clinical information, and expenditure-related costs. Multivariate analysis of economic cost was performed using a generalised linear gamma conjugate model (A1). Results The responses to 102 questionnaires were analysed. The median direct economic cost incurred for the diagnosis of mitochondrial disease was $8,520.19, with direct medical and non-medical costs of $6,769.06 and $2,092.98, respectively, and an indirect cost of $3,162.93. Healthcare insurance covers 27.29% of direct medical expenses. Multivariate analysis showed that the economic cost of diagnosing mitochondrial diseases was significantly correlated with the year of disease onset (P < 0.001). The median annual economic cost for treatment and symptom management after diagnosis was $12,292.79, with direct medical and non-medical costs of $10,887.53 and $1,360.44, respectively, and an indirect cost of $5,442.21. Healthcare insurance covered only 15.16% of direct medical expenses. No significant differences were observed between the subgroups after diagnosis and the annual economic costs of treatment or symptom management. Conclusion The study findings indicated that the economic burden of both the diagnosis and treatment of patients with mitochondrial diseases was substantial. Increased emphasis should be placed on primary and secondary prevention strategies to further reduce the overall economic burden of rare genetic diseases, such as mitochondrial diseases.